1996
DOI: 10.1016/s0006-3495(96)79691-1
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding as a precursor of turbulent electrical activity in cardiac muscle

Abstract: In cardiac tissue, during partial blockade of the membrane sodium channels, or at high frequencies of excitation, inexcitable obstacles with sharp edges may destabilize the propagation of electrical excitation waves, causing the formation of self-sustained vortices and turbulent cardiac electrical activity. The formation of such vortices, which visually resembles vortex shedding in hydrodynamic turbulent flows, was observed in sheep epicardial tissue using voltage-sensitive dyes in combination with video-imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
105
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 20 publications
8
105
0
Order By: Relevance
“…19) and to the catalytic CO oxidation on a platinum surface [207]. Cabo et al pointed out that such a vortex shedding at obstacles to propagation may be behind formation of spirals in cardiac tissue [145].…”
Section: Geometry Effectsmentioning
confidence: 99%
“…19) and to the catalytic CO oxidation on a platinum surface [207]. Cabo et al pointed out that such a vortex shedding at obstacles to propagation may be behind formation of spirals in cardiac tissue [145].…”
Section: Geometry Effectsmentioning
confidence: 99%
“…However, Cabo et al (10) found that spiral formation at an inexcitable barrier in sheep epicardial tissue occurred only if the interval between stimuli did not exceed Ͼ10% of the refractory period of the tissue. A similar condition has also been proposed theoretically by Pertsov et al (50).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that when an electrical wave bends around an inexcitable strip, the wave detaches from the boundary with the formation of a tip; this tip eventually evolves into a rotating spiral wave. This effect was then studied theoretically and experimentally by Cabo et al (10) in sheep epicardial tissue, by using voltagesensitive dyes and video imaging techniques, under the influence of high-frequency stimulations or with partial blockage of the Na ϩ channels of the myocyte cell membrane. Such destabilization led to the formation of self-sustained vortices of electrical activity in the heart, in a manner similar to vortex shedding in hydrodynamic flows past obstacles (73).…”
mentioning
confidence: 99%
“…[5]. The waves of excitation in cardiac tissue that initiate cardiac contraction are also being intensively studied, as abnormal wave propagation in the heart may lead to the formation of vortices and results in dangerous cardiac arrhythmias [6,7]. The key parameter that characterizes a propagating wave is its velocity; it turns out that the velocity of wave propagation in RD systems is affected by several factors, the curvature of the wave front being one of the most important.…”
mentioning
confidence: 99%
“…A highly important emergent phenomenon is wave propagation, which is found in many RD systems such as flame-front propagation [1], waves in the Belousov-Zhabotinsky reaction [2], chemotactic signaling during morphogenesis of a social amoeba [3], waves of intracellular calcium [4], and electrical signaling in neuronal tissue [5]. The waves of excitation in cardiac tissue that initiate cardiac contraction are also being intensively studied, as abnormal wave propagation in the heart may lead to the formation of vortices and results in dangerous cardiac arrhythmias [6,7]. The key parameter that characterizes a propagating wave is its velocity; it turns out that the velocity of wave propagation in RD systems is affected by several factors, the curvature of the wave front being one of the most important.…”
mentioning
confidence: 99%